Analisis Pengaruh Struktur Modal Dan Profitabilitas Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Industri Pertanian Yang Terdaftar Di Bei Periode 2018-2022 - Rifandi, Muhamad; Aviany, Rahmawati Nur (Politeknik Negeri Ambon, 2024)
The company value in this study is proxied by Price Book Value, which is the market ratio used to measure stock prices with the book value of shares. This study aims to test and determine the effect of capital structure proxied by Debt to Equity Ratio and Profitability proxied by Return on Equity on the value of companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling with a total sample of 25 companies and the research data amounted to 125 data for the period 2018-2022. This study used time series data with multiple linear regression models. Hypothesis testing shows the regression coefficient value of the capital structure variable is -0.009 with a significance of 0.433> 0.05. Meanwhile, the regression coefficient value of profitability variable was 0.166 with a significance of 0.009 <0.05. The results of this study indicates that capital structure (DER) has a negative and insignificant effect on firm value, meaning that if the capital structure increases by one unit, the firm value will remain constant. While profitability (ROA) has a positive and significant effect on firm value (PBV), meaning that Profitability (ROA) has a significant effect on Firm Value in Manufacturing companies listed on the IDX that if profitability increases by one unit, the company value will increase.